Modelling the influences of family functioning on the caries experience of children with special needs - Anwar, Diyana Shereen (2024)
WHO has estimated that around 1.3 billion individuals, representing 16% of the global population, live with a significant disability. One of the main concerns raised by this demographic is oral health inequalities. However, the burden of disease for this group in Malaysia has not been thoroughly explored, as well as the psychosocial pathway of oral diseases in this population. Objectives: This study aimed to assess the prevalence of dental caries among Children with Special Needs (CWSN) population based on the disability type, as well as investigate the impact of family functioning on their caries experience. Enamel fluorosis, periodontal status, dental erosion, dental trauma, and oral mucosal lesions were also assessed. Methods: CWSN aged 3 to 12- years-old who attended Community-Based Rehabilitation (CBR) centres were selected using a multistage sampling method for this cross-sectional study. A clinical examination according to WHO Oral Health Assessment Survey for Children was performed. The primary caregiver was requested to provide details regarding the sociodemographic background, oral health practices administered to the CWSN, and how these practices influence the CWSN's oral health-related quality of life (OHRQoL) using the Oral Health Impact Profile (S-OHIP (M). Additionally, the caregiver was asked to report on family functioning using the McMaster Family Assessment Device (FAD). Ethics approval was obtained from the Universiti Teknologi MARA ethics committee (REC/03/2021 (MR/141)) and the Department of Social Welfare Malaysia (JKMM 100/12/5/2:2023/003, JKMM 100/12/5/2:2021/168).